2021
DOI: 10.1111/jgs.17508
|View full text |Cite
|
Sign up to set email alerts
|

Change in central nervous system‐active medication use following fall‐related injury in older adults

Abstract: Background: Central nervous system (CNS)-active medication use is an important modifiable risk factor for falls in older adults. A fall-related injury should prompt providers to evaluate and reduce CNS-active medications to prevent recurrent falls. We evaluated change in CNS-active medications up to 12 months following a fall-related injury in community-dwelling older adults compared with a matched cohort without fall-related injury.Methods: Participants were from the Adult Changes in Thought study conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Increased risk of fall injury associated with BZD use has been recognized for over 30 years [27,28], yet prescribing to older adults remains high [6], and BZD prescriptions are rarely changed even after a fall [29]. Prior analyses of the association between BZD regimen and risk of injury have focused on the risk of use versus non-use [19,20,30], but in the face of such persistent use, clinicians and patients may benefit from a more nuanced characterization of risk among those prescribed BZD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased risk of fall injury associated with BZD use has been recognized for over 30 years [27,28], yet prescribing to older adults remains high [6], and BZD prescriptions are rarely changed even after a fall [29]. Prior analyses of the association between BZD regimen and risk of injury have focused on the risk of use versus non-use [19,20,30], but in the face of such persistent use, clinicians and patients may benefit from a more nuanced characterization of risk among those prescribed BZD.…”
Section: Discussionmentioning
confidence: 99%
“…The American Geriatrics Society/British Geriatrics Society Clinical Practice Guideline for Prevention of Falls in Older Persons recommends annual fall risk screening for adults ≥65 [33], while a recent review of fall prevention for community-dwelling older adults highlighted medication review as a key component of fall risk assessment [34]. Somewhat paradoxically, however, in clinical practice CNS-active medications are generally not being reduced after older adults experience fall injury [29]. Based on our analysis, first it is important for clinicians to recognize-and counsel patients appropriately-that older adults who receive a short-term BZD prescription are not necessarily at lower risk of fall injury.…”
Section: Discussionmentioning
confidence: 99%
“…Certain medications may increase the likelihood of falls among the elderly (Gillespie et al, 2012;Hopewell et al, 2018). Hart et al (2022) found that the dose of CNSactive medications, which include antidepressants, opioids, and benzodiazepines, was not reduced appreciably following a fallrelated injury in older adults. This suggests that adjustment in CNS-active medications is not being utilized adequately to modify fall risk.…”
Section: Tbi and Falls In Older Personsmentioning
confidence: 99%